Role of myrmekites and associated deformation fabrics in controlling development of granitic mylonites in the Pofadder Shear Zone, Southern Namibia - Cisneros Lazaro, Deyanira Graciela (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.